New compound ChlA-F induces autophagy-dependent anti-cancer effect via upregulating Sestrin-2 in human bladder cancer. (1st November 2018) - Hua, Xiaohui; Xu, Jiheng; Deng, Xu; Xu, Jiawei; Li, Jingxia; Zhu, David Q.; Zhu, Junlan; Jin, Honglei; Tian, Zhongxian; Huang, Haishan; Zhao, Qin-shi; Huang, Chuanshu
Abstract: ChlA-F is a novel conformation-derivative of Cheliensisin A, styryl-lactone isolates that show potent anti-tumor potential in vivo and vitro . However, the anti-cancer activity and its potential mechanisms underlying ChlA-F action have never been explored. In the present study, we evaluated the potency of ChlA-F on autophagy-mediated anchorage-independent growth inhibition in human high-grade invasive bladder cancer (BC) cells. We found that ChlA-F treatment significantly inhibited anchorage-independent growth of human BC cells by inducing autophagy in a Sestrin-2 (SESN2)-dependent fashion. Our results revealed that ChlA-F treatment specifically induced SESN2 expression via increasing its transcription and mRNA stability. On one hand, ChlA-F treatment markedly attenuated Dicer protein abundance, in turn abolishing miR-27a maturation and further relieving miR-27a binding directly to SESN2 mRNA 3′UTR, thereby promoting SESN2 mRNA stabilization. On the other hand, ChlA-F treatment promoted Sp1 abundance and consequently mediated SESN2 transcription. These results demonstrate that its activation of the autophagic pathway through specifically promoting SESN2 expression mediates the anti-cancer effect of ChlA-F, which offers insights into the novel anti-cancer effect of ChlA-F on BC, as well as providing therapeutic alternatives against human BC. Highlights: The anti-cancer activity and its potential mechanisms underlying ChlA-F action is first explored. ChlA-F treatment significantly inhibited anchorage-independent growth of human BC cells by inducing autophagy in a SESN2-dependent fashion. ChlA-F treatment specifically induced SESN2 expression via increasing its transcription and mRNA stability. The study of the anti-cancer effect of ChlA-F on BC provides therapeutic alternatives against human BC.